2016
DOI: 10.3996/092015-jfwm-091
|View full text |Cite
|
Sign up to set email alerts
|

Age, Growth, and Fall Diet of Channel Catfish in Cheat Lake, West Virginia

Abstract: Acidification has historically impaired Cheat Lake's fish community, but recent mitigation efforts within the Cheat River watershed have improved water quality and species richness. Presently, channel catfish Ictalurus punctatus are abundant and attain desirable sizes for anglers. We evaluated the age, growth, and fall diet of the population. We collected a sample of 155 channel catfish from Cheat Lake from 5 August to 4 December 2014, a subset of which we aged (n = 148) using lapillus otoliths. We fit four gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…The mean confidence scores for the per-capita growth rates of several prey (common carp, gizzard shad and emerald shiner) are 94%, 80% and 77% respectively, suggesting a high likelihood of their intrinsic population growth in the absence of other fish species. Although the mean confidence scores for almost all species interactions are low, the most probable interaction we inferred is a positive impact of emerald shiner on channel catfish with a 70% level of confidence, which agrees with empirical observations that emerald shiner support channel catfish's growth by serving as major food sources [31]. To refine these predictions, we applied the same network inference procedure to fish abundance time-series data from the Pool 26-the closest pool to the LG pool ( Fig.…”
Section: Probabilistic Inference Of Native Fish Species' Growth and Isupporting
confidence: 86%
See 1 more Smart Citation
“…The mean confidence scores for the per-capita growth rates of several prey (common carp, gizzard shad and emerald shiner) are 94%, 80% and 77% respectively, suggesting a high likelihood of their intrinsic population growth in the absence of other fish species. Although the mean confidence scores for almost all species interactions are low, the most probable interaction we inferred is a positive impact of emerald shiner on channel catfish with a 70% level of confidence, which agrees with empirical observations that emerald shiner support channel catfish's growth by serving as major food sources [31]. To refine these predictions, we applied the same network inference procedure to fish abundance time-series data from the Pool 26-the closest pool to the LG pool ( Fig.…”
Section: Probabilistic Inference Of Native Fish Species' Growth and Isupporting
confidence: 86%
“…Then we were wondering if their values inferred from data provide any evidence that the 9 native fish species grow and interact with each other. To answer this question, we tested the [42], CNCF-BLGL [43], CNCF-ERSN [31], CNCF-GZSD [31], FWDM-GZSD [44], WTBS-BKCP [45], WTBS-BLGL [5], WTBS-FWDM [45], WTBS-ERSN [46], WTBS-GZSD [46], WTBS-CARP [35] (the former species is a predator and the latter species is a prey) null hypothesis for each parameter of each individual ensemble member gLV model that its value is equal to zero. If the p value of this test is p, then 1 − p (what we call the "confidence score" below) informs how likely the parameter is different than 0 since its 100(1 − p)% confidence interval just touches 0.…”
Section: Probabilistic Inference Of Native Fish Species' Growth and Imentioning
confidence: 99%
“…Studies also support that prey quality and abundance contribute to Yellow Perch growth, where robust benthic invertebrate communities promote faster growth than situations where fish rely on zooplankton (Lott et al 1996;Tyus and Knight 2001). Further, growth studies on other species (Channel Catfish Ictalurus punctatus and Walleye) have also observed fast growth (Hilling et al 2016;D.M. Smith, unpublished data), indicating additional unknown factors may facilitate rapid growth of fishes in Cheat Lake.…”
Section: Discussionmentioning
confidence: 94%
“…For modeling of Walleye growth in Cheat Lake we fit three different growth models to length at age data and used an information theoretic approach to select the best fitting model (Katsanevakis 2006;Katsanevakis and Maravelias 2008;Taylor 2013;Hilling et al 2016). Given sexual dimorphism in growth of Walleyes, we analyzed growth separately for males and females .…”
Section: Discussionmentioning
confidence: 99%
“…Otoliths were prepared for aging by cracking them in half perpendicular to their longitudinal axis . We sanded otoliths using 400 or 600 grit wet/dry sandpaper and polished them with 1200 and/or 2500 grit sandpaper to improve visibility of annuli Hilling et al 2016). Otoliths were then placed in a basin of black modeling clay filled with water with the fractured side up to improve clarity (Taylor 2013).…”
Section: Laboratory Processingmentioning
confidence: 99%